The Changing Role of Personal Resources in Perceived Employability of Young People in Different Labor Conditions, Tee Hwa Low - Low, Tee Hwa; Ramos, José; Hernández, Ana (Madrid : Colegio Oficial de Psicólogos de Madrid, 2020)
Personal resources and labor market are factors that contribute to perceived employability. However, how changing labor market conditions affect the relationship between personal resources like career enhancing strategies, personal initiative, and career passivity with self-perceived employability remains unclear. Recent events in Spain give an opportunity to examine if personal resources predict perceived employability differently during normal and harsh labor conditions. Two representative samples of young people were surveyed during a normal labor condition (in 2008, before the big recession, n = 1,992) and a harsh condition (in 2011, with 46% young unemployment rate, n = 1,208). We carried out a multi-group regression in AMOS, and regression coefficient comparisons. Results showed no difference in how career- enhancing strategies predict employability in both conditions. Personal initiative predicts perceived employability only in a normal condition, whereas career passivity increase its predictive strength on employability during a harsh labor condition. Findings can be useful for career services in offering more targeted support to young people when labor conditions become challenging.
En inglés; resúmenes en español e inglés.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Descripción basada en Journal of work and organizational psychology, vol. 36, n. 2 (August 2020), P. 169-179.
Recurso electrónico. Santa Fe, Arg.: elibro, 2024. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Condiciones laborales adversas; Empleabilidad percibida; Estrategias de mejora de carrera; Iniciativa personal; Pasividad de carrera; Artículos electrónicos.